2000
DOI: 10.1088/0953-4075/33/17/101
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous excitation-ionization of helium at five times threshold

Abstract: We report on (e, 2e) experiments for excitation-ionization of helium made in asymmetric geometry at intermediate incident energy and low momentum transfer. The results are compared with Born 1 calculations. Some degree of agreement is obtained and seems to be improved by correction for post-collision interactions. But it cannot be expected that such simple models will correctly reproduce processes that depend so strongly on correlations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
24
0

Year Published

2000
2000
2013
2013

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(28 citation statements)
references
References 19 publications
(30 reference statements)
4
24
0
Order By: Relevance
“…Even for the coplanar geometry, significant discrepancies between theory and experiment can occur under such conditions, if the part of the projectile-target interaction responsible for ionization is accounted for only to first order [12]. Such experiments were performed by Dupré et al [13] and later by Avaldi et al [14] and Rouvellou et al [15]. For their conditions of highly asymmetric energy sharing between the two outgoing electrons, hybrid methods based upon a perturbative treatment, up to second order, of the projectile-target interaction and an R matrix (closecoupling) approach for the ejected-electron-residual-ion interaction [16] were quite successful, especially when the latter part of the problem (e-He collisions) was systematically driven to convergence [17].…”
mentioning
confidence: 99%
“…Even for the coplanar geometry, significant discrepancies between theory and experiment can occur under such conditions, if the part of the projectile-target interaction responsible for ionization is accounted for only to first order [12]. Such experiments were performed by Dupré et al [13] and later by Avaldi et al [14] and Rouvellou et al [15]. For their conditions of highly asymmetric energy sharing between the two outgoing electrons, hybrid methods based upon a perturbative treatment, up to second order, of the projectile-target interaction and an R matrix (closecoupling) approach for the ejected-electron-residual-ion interaction [16] were quite successful, especially when the latter part of the problem (e-He collisions) was systematically driven to convergence [17].…”
mentioning
confidence: 99%
“…In a recent paper Rouvellou et al (2000) reported new measurements of (e, 2e) excitationionization of ground state helium to He + (n = 2) at an impact energy of 365.8 eV. These measurements were made in coplanar asymmetric geometry and their purpose was to extend to lower energies the available data in this geometry (Stefani et al 1990, Dupré et al 1992, Avaldi et al 1998.…”
mentioning
confidence: 99%
“…However, the comparison between these predictions and the experimental data obtained by Stefani et al [9], Bellm et al [10,11], Dürr et al [12], Rouvellou et al [13], and Dogan and Crowe [14] shows that the agreement is far from being perfect. On the one hand, higher-order contributions could be significant.…”
Section: Introductionmentioning
confidence: 82%